2013
DOI: 10.1111/codi.12134
|View full text |Cite
|
Sign up to set email alerts
|

Is colectomy for fulminant Clostridium difficile colitis life saving? A systematic review

Abstract: Aim It is unclear whether colectomy for fulminant Clostridium difficile colitis (FCDC) leads to a improvement in survival compared with continued medical therapy for this moribund population.Method Selected studies from 1994-2010 were identified through a comprehensive search theme applied to MEDLINE (OvidSP and PubMed), EMBASE and by hand searching. Data regarding mortality rates between medically and surgically treated patients were extracted. Risk of bias was assessed using a Newcastle-Ottawa Scale score. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 51 publications
2
40
0
Order By: Relevance
“…We decided not to include fecal transplantation and fidaxomicin because of the limited accessibility in clinical practice. We also did not include colectomy since many patients with cirrhosis may have high mortality risk precluding surgery [22,40]. Thirdly, we did not consider patients with severe C. difficile colitis because the cohort patient population studied were asymptomatic patients hospitalized with cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…We decided not to include fecal transplantation and fidaxomicin because of the limited accessibility in clinical practice. We also did not include colectomy since many patients with cirrhosis may have high mortality risk precluding surgery [22,40]. Thirdly, we did not consider patients with severe C. difficile colitis because the cohort patient population studied were asymptomatic patients hospitalized with cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis by Stewart et al demonstrated that patients with fulminant C. difficile colitis were more likely to survive with emergent colectomy than continued medical treatment. 94 The literature regarding this topic is limited, and the included studies consistently failed to identify indications for surgery as well as criteria for determining non-surgical candidates. Furthermore, this metaanalysis was largely limited to short-term 30-day outcomes.…”
Section: Identification Of Surgical Patientsmentioning
confidence: 99%
“…Furthermore, this metaanalysis was largely limited to short-term 30-day outcomes. 94 Based on current evidence, colectomy should be performed prior to the development of shock and vasopressor requirement, end organ failure, and mental status changes in order to minimize the risk of mortality. 57 , 92 , 93 , 95 A meta-analysis by Bhangu et al examined predictors of post-operative mortality.…”
Section: Identification Of Surgical Patientsmentioning
confidence: 99%
“…The true benefit of the use of rectally administered vancomycin as an adjunctive therapy is not known, as the evidence is limited to case reports [12,13]. Prompt surgical evaluation has been recommended in patients with complicated CDAD as early intervention such as subtotal or total colectomy with end ileostomy can reduce mortality [14,15]. Fidaxomicin was approved for treating CDAD in 2011; however randomized studies have demonstrated similar cure rates between fidaxomicin and oral vancomycin with lower recurrence rate among patients treated with fidaxomicin [16,17].…”
Section: Discussionmentioning
confidence: 99%